Nonlinear Insulin to Carbohydrate Rule for Treatment of Type 1 Diabetes. Issue 11 (2015) - Goodwin, Graham C.; Carrasco, Diego S.; Medioli, Adrian M.; King, Bruce R.; Stephen, Carly
Abstract: This paper develops a nonlinear insulin to carbohydrate rule for use by type 1diabetes patients. The goal is to refine the commonly used Insulin to Carbohydrate Ratio (ICR) formula. The latter is a strictly linear rule relating carbohydrates consumed to insulin infusion. The new relationship presented in this paper is nonlinear and depends on the availability of a nonlinear dynamic model describing a patient's blood glucose response to food and insulin. Such a model can be obtained by use of nonlinear system Identification tools applied to patient test data. The suggested procedure is of similar complexity to the existing standard ICR rule. Hence it has the potential to be of clinical importance especially in developing countries where sophisticated solutions such as an artificial pancreas are unlikely to be used due to excessive cost. Simulations are presented which show that there exists a significant difference between the suggested insulin provided by the rule developed here and that given by the standard ICR rule.